Development of a Headspace-Solid Phase Microextraction-Gas Chromatography/Mass Spectrometry (HS-SPME-GC/MS) Method for the Determination of Benzene in Soft Drinks - Arisseto, Adriana Pavesi; et. al. (2013)
A method based on headspace-solid phase microextraction and gas chromatography with mass spectrometry has been developed and validated for the determination of benzene in soft drinks. The extraction step was optimized using a rotatable central composite design including the following experimental variables: extraction temperature, extraction time, sample weight, and salt concentration. The optimized procedure, which was carried out at 30 °C during 30 min by using a 75 μm carboxen-polydimethylsiloxane fiber, showed good linearity within the concentration range 0–25 μgkg−1 (r2>0.999), mean recoveries from 97.5 to 103.1 %, and coefficients of variation from 1.5 to 13.4 % for repeatability and from 1.5 to 15.7 % for withinlaboratory reproducibility. Limits of detection and quantification were calculated at 0.02 and 0.08 μgkg−1, respectively. The method was applied to determine the concentrations of benzene in 77 samples of beverages from the Brazilian market. Levels from <0.08 to 10.84 μgkg−1 were obtained, which are comparable to those verified in other countries. Most of the samples (72.2 %) contained benzene up to 1 μgkg−1.